Women’s autonomy and utilization of maternal health care services in rural Nepal - Lamichhane, Kamala (Nepal Population Journal, 2018)
Nepal has one of the highest maternal mortality ratios in South Asia although the situation is improving in recent days. One of the reasons for such a high mortality may be attributed to the under-utilization of modern maternal health services during pregnancy. This study has analyzed the relationship between women’s autonomy and the utilization of maternal health care services in order to explore some possible reasons for the under-utilization of the services. Data from the Nepal demographic and Health Survey, 2011 is used for the study. The analysis is based on 2374 married women aged 15-49 years who had given a live birth during three years preceding the survey. Women's household decision making power, control over use of earning and decision on using contraception have been used to explore the indicators of women's autonomy. Logistic regression is used to assess the net effect of several independent variables on two dependent variables (adequate antenatal care and institutional delivery) of maternal health care. Logistic regression analyses reveal that the utilization of both maternal health care services are related to women's autonomy as indicated by decision making power on own health care, large household purchases and control over earnings because financial sufficiency is must at that period. Women's’ decision-making power appears to be the most powerful predictors for increasing maternal health service utilization. The study results suggest that policy actions that increase women’s autonomy at home could be effective in helping assure good maternal health.